Urgensi Pengaturan tentang Mekanisme Pelaksanaan Pemberian Hak Akses Jalan (Hak Servituut) - Siti Muadah (Jurnal Hukum Lex Generalis, 2025)
Land rights holders are not permitted to use their land for their personal interests only, but must also pay attention to the interests of the community as intended by Article 6 of the UUPA regarding land having a social function. This study uses a normative method with qualitative analysis to obtain the results of this study, explaining that the principle of the social function of land rights as regulated in Article 6 in the application of servitude rights (yard devotion) for public road access has not provided legal certainty regarding the concept of compensation for land owners who provide road access. Closing road access for the community carried out by the heirs as owners of the land based on SHM No. 4435 is an unlawful act because the road access has been provided by the parents of the heirs at the time of the sale and purchase transaction supported by the Regent's Decree Number: 35 / EF-P / LF / VIII / 1997, dated August 27, 1997 concerning the provision of land for road access and parking lots.